Analysis and prediction of serological indicators associated with colorectal interval polyposis after resection - Lan, Yuan; Zhang, Li; Li, Ren Jun (Frontiers in Endocrinology, 2025)
BackgroundThe examination of the endoscope and the subsequent rediscovery of polyps after endoscopic intervention presents a significant clinical challenge. Multiple factors may contribute to this phenomenon. This study aimed to identify determinants of interval polyposis by analyzing common serological markers and polyp-related variables, ultimately developing a predictive model.MethodsThis retrospective study included 415 patients diagnosed with colorectal polyps who underwent either endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD) at Chaohu Hospital affiliated with Anhui Medical University between December 1, 2022 and December 31, 2023. The primary objective was to evaluate associations between hematologic indicators, polyp-related characteristics, and the risk of rediscovery colorectal polyps. Interval polyposis was defined as the detection of one or more polyps within 18 months after the initial polypectomy, regardless of anatomical location. Follow-up data were obtained through electronic medical records, including demographic information (age, sex, smoking and alcohol use, hypertension, and diabetes history), anthropometric measures (weight, height, BMI), surgical details, polyp features (location, size, number, histological type), and relevant serological parameters.ResultsSignificant differences were observed between the non-interval polyposis and interval polyposis groups in terms of hypertension, diabetes, triglycerides (TG) and the number of polyps (P < 0.05). Binary logistic regression analysis identified four independent risk factors: hypertension (OR, 2.741; 95% CI, 1.451-5.179), diabetes (OR, 4.828; 95% CI, 1.943-11.995), number of polyps (OR, 1.211; 95% CI, 1.078-1.361) and triglyceride levels (OR, 1.823; 95% CI, 1.303-2.551).ConclusionHypertension, diabetes, an increased number of polyps and elevated triglyceride levels are independent predictors of colorectal interval polyposis following endoscopic resection. These findings underscore the importance of monitoring blood pressure, blood sugar, triglyceride levels and conducting regular colonoscopic surveillance in high-risk individuals to facilitate early detection and management of interval polyposis.